Influence Analysis of the Antifriction Layer Materials and Thickness on the Contact Interaction of Spherical Bearings Elements - Anatoliy A. Adamov; Anna A. Kamenskikh; Anastasia P. Pankova (Lubricants, 2022)
Bearings are the supporting elements of bridges. They perceive vertical and horizontal loads from the bridge span. Spherical bearings are one of the construction common types. The material and configuration of the anti-friction layers determine the bearing performance. The paper performed the contact deformation analysis of spherical bearing elements at a nominal vertical load of 1000 kN. The six types of the spherical sliding layer material are considered: ultra-high molecular weight polyethylene (UHMWPE) from three different manufacturers, modified polytetrafluoroethylene (PTFE), and composite materials by PTFE with two different forms of reinforcing bronze inclusions. Young’s modulus, Poisson’s ratio, and strain curve are obtained experimentally for spherical sliding layer materials. Paper considered the influence of the sliding layer material on the contact parameters and deformation characteristics of the structure with a standard interlayer thickness by 4 mm. Research observed significant the composite interlayer deformation and the appearance of “no contact” zones on the mating surfaces. The option of increasing the sliding layer thickness up to 6–8 mm is considered. A decrease is observed in the maximum level of contact parameters by increase of the sliding layer thickness. The influence of the anti-friction layer materials becomes insignificant on the bearing deformation with an increase of the spherical sliding layer thickness.